Konsep dan Masalah Penerapan Metode Pembelajaran: Upaya Peningkatan Mutu Pembelajaran Melalui Konsistensi Teoretis-Praktis Penggunaan Metode Pembelajaran - Agus Wedi (Edcomtech: Jurnal Kajian Teknologi Pendidikan, 2016)
One of the indicators that causes the low quality of learning in schools is the theoretical inconsistency — the practical use of learning methods. In the context of the implementation of learning in which the method is an integral part of it, the fundamental problem is none other than the failure to implement the learning method optimally as mandated at the theoretical level. This is where the need for revitalizing theoretical consistency - the practical use of learning methods.